Prevalence and risk factors of soil transmitted helminth infections among school-aged children in Garut, Indonesia: Insights from a six-year deworming intervention - Endang Puji Astuti; Joni Hendri; Yuneu Yuliasih; Rizal Pratama Sulaeman; Tri Isnani; Sugiyono Saputra; Herjuno Ari Nugroho; Pandji Wibawa Dhewantara; Indah Kartika Murni (Asian Pacific Journal of Tropical Medicine)
Objective: To assess prevalence and factors associated with soil-transmitted helminth (STH) infections among rural school children. Methods: This school-based survey applied a cross-sectional design which included children aged 6-14 years enrolled in 12 elementary schools in Banjarwangi, Garut, West Java Province. Stool and blood samples were collected from 388 randomly selected students to examine the STH infections and anemia status, respectively. Anthropometric assessment was performed to profile nutritional status. A structured questionnaire was employed to collect socio-demographic and school performance data. Multivariable logistic regression models were built to assess the factors associated with STH infections in school children. Results: Among 386 schoolchildren, 9.8% children were positive for one or more STH infections, predominantly Trichuris trichiura (9.0%), with males (n=23), significantly more infected than females (n=13) (5.9% vs. 3.4%, P=0.04). The most infected age group was 6-10 years (n=25, 6.5%). The prevalence of STH infection was significantly higher among students that practicing open defecation (n=22, 5.7%) (P=0.03). The odds risk of STH infections was associated with practicing open defecation (aOR 2.54, 95% CI 1.17-5.53, P=0.02). Conclusions: The findings from this study demonstrate the persistent STH transmission among children underscoring the need for sustained post-MDA intervention strategies in resource-limited settings.